Categorized Genetic Analysis in Childhood-Onset Cardiomyopathy. (October 2020) - Al-Hassnan, Zuhair N.; Almesned, Abdulrahman; Tulbah, Sahar; Alakhfash, Ali; Alhadeq, Faten; Alruwaili, Nadiah; Alkorashy, Maarab; Alhashem, Amal; Alrashdan, Ahmad; Faqeih, Eissa; Alkhalifi, Salwa M.; Al humaidi, Zainab; et al.
Abstract : Background: Childhood-onset cardiomyopathy is a heterogeneous group of conditions the cause of which is largely unknown. The influence of consanguinity on the genetics of cardiomyopathy has not been addressed at a large scale. Methods: To unravel the genetic cause of childhood-onset cardiomyopathy in a consanguineous population, a categorized approach was adopted. Cases with childhood-onset cardiomyopathy were consecutively recruited. Based on the likelihood of founder mutation and on the clinical diagnosis, genetic test was categorized to either (1) targeted genetic test with targeted mutation test, single-gene test, or multigene panel for Noonan syndrome, or (2) untargeted genetic test with whole-exome sequencing or whole-genome sequencing. Several bioinformatics tools were used to filter the variants. Results: Two-hundred five unrelated probands with various forms of cardiomyopathy were evaluated. The median age of presentation was 10 months. In 30.2% (n=62), targeted genetic test had a yield of 82.7% compared with 33.6% for whole-exome sequencing/whole-genome sequencing (n=143) giving an overall yield of 53.7%. Strikingly, 96.4% of the variants were homozygous, 9% of which were found in 4 dominant genes. Homozygous variants were also detected in 7 novel candidates ( ACACB, AASDH, CASZ1, FLII, RHBDF1, RPL3L, ULK1 ). Conclusions: Our work demonstrates the impact of consanguinity on the genetics of childhood-onset cardiomyopathy, the value of adopting a categorized population-sensitive genetic approach, and the opportunity of uncovering novel genes. Our data suggest that if a founder mutation is not suspected, adopting whole-exome sequencing/whole-genome sequencing as a first-line test should be considered. Abstract : Supplemental Digital Content is available in the text.